El paisaje: un texto para leer - Tanács, Erika (Pontificia Universidad Javeriana, 2014)
The objective of this work is, first, to offer a general reflection on the production of the use of landscape as a constitutive component of social and political processes. Second, the work attempts to examine how and why social life, values, principles and criteria of a society or a community can be built, reinforced an even disputed through landscape. Finally the work analyzes the mechanisms of codification and transmission of this information, that, through phyisical forms, architectural elements or spatial dispositions, are able to translate the explicit knowledge from one form of expression to another.